If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(X + 3) + 2(3x + -2) = 58 Reorder the terms: 2(3 + X) + 2(3x + -2) = 58 (3 * 2 + X * 2) + 2(3x + -2) = 58 (6 + 2X) + 2(3x + -2) = 58 Reorder the terms: 6 + 2X + 2(-2 + 3x) = 58 6 + 2X + (-2 * 2 + 3x * 2) = 58 6 + 2X + (-4 + 6x) = 58 Reorder the terms: 6 + -4 + 2X + 6x = 58 Combine like terms: 6 + -4 = 2 2 + 2X + 6x = 58 Solving 2 + 2X + 6x = 58 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 2X + -2 + 6x = 58 + -2 Reorder the terms: 2 + -2 + 2X + 6x = 58 + -2 Combine like terms: 2 + -2 = 0 0 + 2X + 6x = 58 + -2 2X + 6x = 58 + -2 Combine like terms: 58 + -2 = 56 2X + 6x = 56 Add '-6x' to each side of the equation. 2X + 6x + -6x = 56 + -6x Combine like terms: 6x + -6x = 0 2X + 0 = 56 + -6x 2X = 56 + -6x Divide each side by '2'. X = 28 + -3x Simplifying X = 28 + -3x
| 7/12x=28/3 | | X(x+3)=x(x+6)-15 | | 1.4+(2.3)= | | Xsquare+3x-4=0 | | 3500+1680x=220650 | | P-19=17 | | 12=-6k+4+2 | | 3a^2+30a+100=0 | | -8=-3k-5k | | log(8x+2)=6 | | -18=5x+4x | | 7(11+1)+5(11+1)=14 | | 3a-5a=8 | | 7(-13+1)+5(-13+1)=14 | | 2n+5+7n=-4 | | x+60=10 | | 6v+7v=-13 | | m+3-7m=-15 | | 6x+64=9x+7 | | xy+5x-y-10=0 | | 1/2x=3/2x-7 | | 7(x+1)+5(x+1)=14 | | -11=n-1+n | | 4x^6+45=40 | | 6x-4+4x=-14 | | 3x-10=10x | | 8+7n-4n=-1 | | z^2(2y)/(3) | | -3(3+8j)= | | n-6-2=-2 | | z^2(2|y)/(3) | | 5+17x-3=9x+12-2x |